Parliamentary rules of procedure and parliamentary speech - Milić Dejan A. (Srpska Politička Misao)
The topic of this work is the regulation of parliamentary debate by parliamentary rules of procedure in order to ensure its smooth flow and quality, and to prevent abuse of freedom of speech. Parliamentary debate is the "blood stream" of parliamentary work and decision-making. In the parliamentary debate, with freedom of speech ensured, parliamentarians oppose political positions, ideas and arguments in their speeches. For the sake of efficient parliamentary work and decision-making, the debate should be regulated legally, which is done by the parliamentary rules of procedure, the "parliamentary constitution" adopted by the parliament and which prescribes the internal organization and procedures of the parliament. The goal of regulating the debate with the rules of procedure is to ensure uninterrupted parliamentary work and decision-making, but also to protect freedom of speech and the rights of the minority in parliament. In order to realize this, parliamentary rules of procedure must be clear, precise and fair. It must not be a mere declarative act, but an expression of the political understanding of opposing political options and their common aspiration for a constructive approach to solving issues of general interest. The parliamentary rules of procedure can only be fair if the political culture of parliamentary officials, a healthy parliamentary tradition and bona fide parliamentary customs are woven into it.